The Cuban National Healthcare System: Characterization of primary healthcare services. - Keli Regina DAL PRÁ; Daniela Schwabe MINELLI; Débora MARTINI; Renata da Rosa Turatti FETZNER; Karine Cardoso FONTANA (Universidade de Brasília, 2015)
This article presents a report on the experience of healthcare professionals in Florianópolis, who took the course La Atención Primaria de Salud y la Medicina Familiar en Cuba [Primary Healthcare and Family Medicine in Cuba], in 2014. The purpose of the study is to characterize the healthcare units and services provided by the Cuban National Healthcare System (SNS) and to reflect on this experience/immersion, particularly on Cuba's Primary Healthcare Service. The results found that in comparison with Brazil's Single Healthcare System (SUS) Cuba's SNS Family Healthcare (SF) service is the central organizing element of the Primary Healthcare Service. The number of SF teams per inhabitant is different than in Brazil; the programs given priority in the APS are similar to those in Brazil and the intersectorial nature and scope of the services prove to be effective in the resolution of healthcare problems.